Laser Treatment of Peri-Implantitis: A Systematic Review of Radiographic Outcomes - Miriam Ting; Leela Subhashini C. Alluri; John G. Sulewski; Jon B. Suzuki; Andre Paes Batista da Silva (MDPI AG, 2022)
(1) Background: This systematic review aimed to evaluate the effects of laser therapy on radiographic bone level (RBL) changes in peri-implantitis defects. (2) Methods: A literature search with defined inclusion criteria was performed. PubMed, Web of Science, Cochrane Library, and Google Scholar were searched through September 2020. The evaluated primary outcomes were RBL changes. In studies that reported RBL data, corresponding secondary clinical outcomes were probing depth (PD), bleeding on probing (BOP), and clinical attachment level (CAL). (3) Results: Thirteen articles were selected for data extraction and risk of bias assessment. Eight studies showed evidence of RBL gain in the laser groups compared to baseline, but did not report the statistical significance. Eight of these 13 studies reported comparisons to control. Five of the eight studies did not show RBL gain in the laser groups compared to control. In the laser groups compared to baseline, 11 of 13 reported reduced PD, and 6 of 13 reported significantly reduced BOP. Compared to the control, eight of the eight reported reduction of PD, and three of six reported significantly reduced BOP. Statistical significance was not consistently reported. (4) Conclusions: Within the limits of this systematic review, laser treatment may promote bone gain in peri-implantitis defects, may reduce BOP and PDs, and may be comparable to mechanical therapy. However, definitive conclusions can only be made with statistically significant data, which were found lacking in the currently available studies. This systematic review was registered with the National Institute for Health Research, international prospective register of systematic reviews (PROSPERO): CRD42020207972.